(untitled) (Altre Modernità, 2023)
Of Armenian descent, though born in Padua and educated in Italy, Vittoria Aganoor (1855-1910) would travel along the peninsula from north to south, spending the last years of her life between Perugia and Magione-Monte del Lago. Along with lyric poetry, letters will play a central role in her experience as a writer, as evidence of a way of life in a pre-technological society. These are pages, some of which are still unpublished, on which this contribution intends to dwell, registering first of all the character of a female narrative, on which movements and encounters affect, highlighting the spirit of a woman who is free and lively, melancholic and tormented, inclined to introject feelings and ideals on which her soul will be nourished. It is also to be noted that the years spent in Umbria, since the dawn of the new century, will constitute a happy part of her existence, witnessed by her falling in love with that land and the landscape, particularly the muffled landscape of Lake Trasimeno, which she will be able to capture with the sensitivity and refinement of an uncommon humanistic education. Traits that still emerge from the correspondences entertained with prominent figures in early 20th-century literary-worldly society, in which Aganoor occupies a non-secondary role, thanks to her aristocratic origins and her subsequent marriage to Perugian deputy Guido Pompilj.